2022
DOI: 10.3389/fendo.2022.978747
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide is a predictor of telomere shortening: A five-year longitudinal study

Abstract: AimRelative telomere length (RTL) predicts the development of many age-related diseases. Yet, few studies have evaluated their longitudinal effect on RTL. We investigated longitudinally the association between cardiometabolic risk factors and RTL.MethodsThis was a longitudinal study with a 5-year follow-up period, based on data collected in 2014 and 2019. Of 478 participants in 2014, 198 consented to be followed-up in 2019. The associations between RTL and risk factors were analyzed using t-test, ANOVA or simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Cross-sectional studies suggest that that insulin resistance is associated with increased telomere shortening in some groups but not in others ( 108 112 ). A positive association was also noted in the follow-up of cohorts ( 113 115 ) with one exception ( 116 ). These observational studies also found an association between telomere attrition and other parameters such as adiposity, hypertension or circulating sirtuin-1 concentrations.…”
Section: Insulin and Aging: Epidemiological Findingsmentioning
confidence: 73%
“…Cross-sectional studies suggest that that insulin resistance is associated with increased telomere shortening in some groups but not in others ( 108 112 ). A positive association was also noted in the follow-up of cohorts ( 113 115 ) with one exception ( 116 ). These observational studies also found an association between telomere attrition and other parameters such as adiposity, hypertension or circulating sirtuin-1 concentrations.…”
Section: Insulin and Aging: Epidemiological Findingsmentioning
confidence: 73%
“…Telomere length is critical for maintaining the divisional capacity of oocytes, and once telomeres are depleted, the cell will immediately initiate the apoptotic program and progress toward apoptosis ( 54 ). One mechanism by which IR-induced hyperglycemic states may promote telomere shortening is through oxidative stress, which produces oxygen free radicals that affect telomere ends, which are enriched with guanine residues, the latter of which make them susceptible to oxidative stress ( 55 ). Oocytes are prone to chromosome segregation errors during meiosis, resulting in aneuploidy, and these factors include crossover problems when recombination occurs in meiotic M I, spindle assembly checkpoint (SAC) deletion, and so on, which may independently induce aneuploidy in oocytes, or they may be interrelated ( 56 ).…”
Section: Ir Affects Assisted Reproduction Pregnancy Outcomes In Infer...mentioning
confidence: 99%